The evolution of museological thinking - Castrillón, Alfonso (2019)
This work addresses the evolution of Museological Thinking from collecting, and going through specialists or technicians, to end with the notion of natural heritage in relation to the populations of both 18th and 19th century. On the other hand, the pedagogical work in the museums of North America is highlighted. In addition, the transcendental role-played by the medical doctor and anthropologist Julio César Tello Rojas in relation to Peruvian archaeology. Finally, it states the New Museology and the French contributions in relation to the Ecomuseum.